Variáveis Geológicas no Comportamento das Razões qc/N em Porto Alegre, RS – Brasil - NAIME, ROBERTO HARB; FIORI, ALBERTO PIO (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> The gathering of geotechnical investigation by SPT and CPT follow geological and environmental criteria, identified in maps, allowed identify different units, influence zones of degree of maturity or geomorphological conditions, influence of fault zones and different alluvial areas, allowed to identify different behavior of ratio qc/N in soils of Porto Alegre city. This work presents the criteria utilized for this differentiation, showing the figures of correlation between qc and N, and figures showing the behavior of K (qc/N) related to the depth, with considerations about the results.